PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURNOVER DAN RETURN ON ASSET TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Muhammadinah, Muhammadinah Muhammadinah (Islamic Economics Program, Faculty of Islamic Economics and Business, 2015)
The aim of this research is to analyze the influence of Current Ratio, Debt To Equity Ratio, Total Asset Turnover, and Return on Asset on Dividen Payout Ratio of consumption good industry sectors companies that are listing in Indonesia Stock Exchange. The population of this research are 38th companies. Sampling technique is conducted based on purposive sampling method on 13th companies with their financial reports disclosure that was listing in Indonesia Stock Exchange. Using multiple regression with t test and F valued, this research finds out that partially only variables of Total Asset Turnover, and Return on Asset that have singnificance effects on Dividen Payout Ratio. But simultaneously all independent variables has significance effect on Dividen Payout Ratio. Key Words: Current Ratio, Debt To Equity Ratio, Total Asset Turnover, Return on Asset, Dividen Payout Ratio, and Indonesia Stock Exchange